INTER/LOC/AÇÃO: A concepção da obra e suas dependências espaciais - Ines Karin Linke Ferreira (2007)
This paper develops a reflection on the conception of the artistic work and its spatial dependencies and searches to reflect on the sensitive andphenomenological dimensions and the exhibition of the work of art based on the discussion of certain plastic and scenic works, which were realized in Belo Horizonte between 2002 and 2007. The paper considers concepts and issues of Theater and Visual Arts to examine the intersection between the two fields and reevaluates the installation and the site to establish the experience as an exchange or a meeting between instances, which are capable of creating new locations andconcepts of realities that are located between art and life. The works are created in regards to and based on elements of everyday life. But how does one create a sense of reality that re-establishes the pleasure of common things? The proposal is to displace the aesthetic space to daily experiences, promote exchange between colleagues and create relations with surrounding places and actions that allow processes of sociability outside and within the institutional space of a gallery. Aiming at articulating an interlocution between visual and theatrical practices, theartist develops procedures such as awareness, appropriation and displacements of existing places and objects to investigate the relationship of objects, places and people within the fields of esthetic experience and artistic action.